Application of laser microprobe mass analysis to the structural investigation - FURUYA, Shiro; FURUYA, Keiichi; ASAMAKI, Tatsuo; KIKUCHI, Tadashi; NADAHARA, Soichi (BUNSEKI KAGAKU, 1985)
Laser microprobe mass analysis(LAMMA) offers the possibility of investigation of various kinds of samples with a high lateral resolution and a high sensitivity. Nevertheless, a mechanism of desorbed ion formation and its fragmentation has not been fully clarified. In this paper, the effects of laser power density on atomic and molecular ion formation were examined. A series of negative carbon cluster ions corresponding to Cn- and CnHm- were observed for organic samples at high laser power density. Characteristic molecular fragment peaks became observed at a reduced power density just over a threshold value. Pyrene and benzo [α] pyrene showed large molecular ion peaks in the positive ion spectra. On the other hand, nitropyrenes did not give positive molecular ion peaks but showed weak molecular ion peaks in the negative ion spectra. Nitropyrenes showed intense peaks of (M-NO)- and (M+O-H)-. The characteristic peaks of (M-NO)-, (M-2NO)-, and (M-3NO)- were observed for mononitropyrene, dinitropyrene, and trinitropyrene, respectively. Sodium dodecyl sulfate was readily detected from their characteristic negative ions, C12H25OSO3-, SO3-, and HSO4-. Pyrite gave peaks of Fe+ and S+ at high power density, while FeS2+, FenSn-1+, and FenSn+ cluster ions were observed when irradiated with low power density. Nonmetallic inclusions on the electroetched surface of a steel gave typical peaks of manganese oxide in the positive ion spectra under low power conditions.